Analisis dan Perancangan Enterprise Campus Area pada Infrastruktur Jaringan Hirarki STIK Bina Husada Palembang Berbasis Cisco Enterprise Model - Wahfiyudin Alkahfi (Institute of Information Technology and Social Science (IITSS), 2021)
The use of internet-based computer networks has become a primary need to support educational activities in the digital era. STIK Bina Husada Palembang, as a health-focused university, utilizes computer networks to support academic and administrative activities. However, the use of networks with large segments and a high number of hosts results in increased broadcast packet traffic and reduced network management performance. This study aims to analyze and design a computer network infrastructure based on a hierarchical model using the Cisco Enterprise Model with an Enterprise Campus Area approach. The method used was a top-down network design method oriented toward user needs. The results of the study include a hierarchical network design that divides the network into several layers, each with its own broadcast domain and service functions, arranged in a structured, modular, and manageable manner. This network design was simulated using Cisco Packet Tracer. The design results are expected to serve as a reference for the future development of STIK Bina Husada Palembang’s network infrastructure.